Computers, the Internet and medical education in Africa. - Williams CD; Pitchforth EL; O'Callaghan C (Medical Education, 2010)
Objectives: This study aimed to explore the use of information and communications technology (ICT) in undergraduate medical education in developing countries. Methods: Educators (deans and heads of medical education) in English-speaking countries across Africa were sent a questionnaire to establish the current state of ICT at medical schools. Non-respondents were contacted firstly by e-mail, subsequently by two postal mailings at 3-month intervals, and finally by telephone. Main outcome measures included cross-sectional data about the availability of computers, specifications, Internet connection speeds, use of ICT by students, and teaching of ICT and computerised research skills, presented by country or region. Results: The mean computer : student ratio was 0.123. Internet speeds were rated as 'slow' or 'very slow' on a 5-point Likert scale by 25.0% of respondents overall, but by 58.3% in East Africa and 33.3% in West Africa (including Cameroon). Mean estimates showed that campus computers more commonly supported CD-ROM (91.4%) and sound (87.3%) than DVD-ROM (48.1%) and Internet (72.5%). The teaching of ICT and computerised research skills, and the use of computers by medical students for research, assignments and personal projects were common. Conclusions: It is clear that ICT infrastructure in Africa lags behind that in other regions. Poor download speeds limit the potential of Internet resources (especially videos, sound and other large downloads) to benefit students, particularly in East and West (including Cameroon) Africa. CD-ROM capability is more widely available, but has not yet gained momentum as a means of distributing materials. Despite infrastructure limitations, ICT is already being used and there is enthusiasm for developing this further. Priority should be given to developing partnerships to improve ICT infrastructure and maximise the potential of existing technology.